How reliable are Functional Movement Screening scores? A systematic review of rater reliability. Issue 9 (27th August 2015) - Moran, Robert W; Schneiders, Anthony G; Major, Katherine M; Sullivan, S John
Abstract : Background: Several physical assessment protocols to identify intrinsic risk factors for injury aetiology related to movement quality have been described. The Functional Movement Screen (FMS) is a standardised, field-expedient test battery intended to assess movement quality and has been used clinically in preparticipation screening and in sports injury research. Aim: To critically appraise and summarise research investigating the reliability of scores obtained using the FMS battery. Study design: Systematic literature review. Methods: Systematic search of Google Scholar, Scopus (including ScienceDirect and PubMed), EBSCO (including Academic Search Complete, AMED, CINAHL, Health Source: Nursing/Academic Edition), MEDLINE and SPORTDiscus. Studies meeting eligibility criteria were assessed by 2 reviewers for risk of bias using the Quality Appraisal of Reliability Studies checklist. Overall quality of evidence was determined using van Tulder's levels of evidence approach. Results: 12 studies were appraised. Overall, there was a 'moderate' level of evidence in favour of 'acceptable' (intraclass correlation coefficient ≥0.6) inter-rater and intra-rater reliability for composite scores derived from live scoring. For inter-rater reliability of composite scores derived from video recordings there was 'conflicting' evidence, and 'limited' evidence for intra-rater reliability. For inter-rater reliability based on live scoring of individual subtests there was 'moderate' evidence of 'acceptable' reliability (κ≥0.4) for 4 subtests (Deep Squat, Shoulder Mobility, Active Straight-leg Raise, Trunk Stability Push-up) and 'conflicting' evidence for the remaining 3 (Hurdle Step, In-line Lunge, Rotary Stability). Conclusions: This review found 'moderate' evidence that raters can achieve acceptable levels of inter-rater and intra-rater reliability of composite FMS scores when using live ratings. Overall, there were few high-quality studies, and the quality of several studies was impacted by poor study reporting particularly in relation to rater blinding.